Niche market of event for village tourism - Ni Made Ernawati; Ayu Trisnayoni Raden; I Wayan Basi Arjana; Ni Putu Lianda Ayu Puspita; Radu Negru (International Journal of Applied Sciences in Tourism and Events, 2022)
This research aims to explore and analyze the potency of community-based rural tourism to organize or be used as a venue for events. This is a qualitative study examining publications related to the issue, as well as the writers' direct experience and involvement in the event taking up the role either as a participant or the event committee member; the study mainly used focus group discussion to explore and generate ideas on the event for village tourism to identify the event-market potential for the Community-based Tourism. The study is conducted to prospect the event for CBT based on the type, purpose, and participants of the event, as well as to assess the facilities available at CBT. The results show that the characteristics and the purpose of events are reflected in the type of events. There are 7 types of event: traditional, natural, and farming-related smaller seminars, exhibitions, festivals, bazaar, sport, education/sharing, spiritual, and personal advancement retreat. For the CBT event, purposes could be created depending on the market's needs, the community's needs, and the facilities available in the tourism village considering the theme and scale of the event. It is expected that the results of the study could be used as a reference in advancing the product-market scheme of rural tourism as well as creating awareness among the prospective parties to hold events and to empower rural tourism to support village development.